ANALISIS YURIDIS PERTANGGUNGJAWABAN PENGURUS TERHADAP ANGGOTA ATAS PENGELOLAAN KOPERASI SIMPAN PINJAM YANG DINYATAKAN PAILIT BERDASARKAN UNDANG-UNDANG NOMOR 25 TAHUN 1992 TENTANG PERKOPERASIAN DIKAITKAN DENGAN PRINSIP KEHATI-HATIAN - Jhonson Datmalem Siahaan; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Cooperatives are a form of cooperation in the economic field which is held on the basis of thesimilarity in the types of fulfillment of life needs. In accordance with the provisions contained in article16 of the Law of the Republic of Indonesia Number 25 of 1992 along with an explanation stated that